Generalization of conditioned disgust and the attendant maladaptive avoidance: Validation of a novel paradigm and effects of trait disgust-proneness. (November 2021) - Berg, Hannah; Hunt, Christopher; Cooper, Samuel E.; Olatunji, Bunmi O.; Lissek, Shmuel
Abstract: Overgeneralization of conditioned fear to safe stimuli that resemble a previously-learned threat-cue is a well-studied correlate of clinical anxiety, yet whether conditioned disgust generalizes remains unknown, as does the extent to which such generalization is associated with disgust-related traits and maladaptive outcomes. The present study addresses this gap by adapting a validated fear-generalization paradigm to assess conditioned disgust and behavioral avoidance to a disgust-cue (CS+) paired with a disgusting video clip, and safe generalization stimuli parametrically varying in perceptual similarity to CS+. For comparison, levels of fear generalization were also assessed using the original fear-generalization paradigm. In both paradigms, costly and unnecessary avoidance to safe threat-cue approximations analogues maladaptive outcomes of generalization. In the disgust paradigm only, disgust-proneness was associated with elevated perceived risk to safe stimuli and increases in the extent to which such elevations were accompanied by maladaptive avoidance. Comparable levels of generalization, and positive associations between generalization and maladaptive avoidance, were found across disgust and fear paradigms. Results confirm that conditioned disgust is subject to generalization, implicate generalized disgust as a source of maladaptive avoidance particularly among those prone to disgust, and suggest a potential role for these processes in the etiology and maintenance of disgust-related disorders. Highlights: Conditioned disgust generalizes to safe stimuli, prompting maladaptive avoidance. Disgust-proneness associated with greater generalization of US-expectancy. Generalized disgust predicts maladaptive avoidance among those prone to disgust. Effects of disgust-proneness seen in disgust- and not fear-conditioning paradigm.